Inelastic electron scattering by the gas phase in near ambient pressure XPS measurements. (7th May 2021) - Pielsticker, Lukas; Nicholls, Rachel; Beeg, Sebastian; Hartwig, Caroline; Klihm, Gudrun; Schlögl, Robert; Tougaard, Sven; Greiner, Mark
Abstract : X‐ray photoemission spectroscopy (XPS) measurements in near‐ambient pressure (NAP) conditions result in a signal loss of the primary spectrum as a result of inelastic scattering of photoelectrons in the gas phase. The inelastic scattering of the primary electrons gives rise to a secondary signal that can result in additional and often unwanted features in the measured spectrum. In the present work, we derive equations that can be used to model the resulting signal and provide equations that can be used to simulate or remove the inelastic scattering signal from measured spectra. We demonstrate this process for photoemission spectra of a wide range of kinetic energies, measured from Au, Ag, and Cu, in a variety of gases (N2, He, H2, and O2 ). The work is supplemented with an open‐source software in which the algorithms described here have been implemented and can be used to remove the gas phase inelastic scattering signal.